The WEE1 regulators CPEB1 and miR-15b switch from inhibitor to activators at G2/M - Kratassiouk, Gueorgui (Cell Cycle, 2016)
MicroRNAs (miRNAs) in the AGO-containing RISC complex control messenger RNA (mRNA) translation by binding to mRNA 3′ untranslated region (3′UTR). The relationship between miRNAs and other regulatory factors that also bind to mRNA 3′UTR, such as CPEB1 (cytoplasmic polyadenylation element-binding protein), remains elusive. We found that both CPEB1 and miR-15b control the expression of WEE1, a key mammalian cell cycle regulator. Together, they repress WEE1 protein expression during G1 and S-phase. Interestingly, the 2 factors lose their inhibitory activity at the G2/M transition, at the time of the cell cycle when WEE1 expression is maximal, and, moreover, rather activate WEE1 translation in a synergistic manner. Our data show that translational regulation by RISC and CPEB1 is essential in cell cycle control and, most importantly, is coordinated, and can be switched from inhibition to activation during the cell cycle.